Micorrización de plantas de PINUS HALEPENSIS, PINUS PINASTER Y QUERCUS ILEX SUBSP. BALLOTA PARA REPOBLACIÓN DE ZONAS INCENDIADAS DE ESCASA REGENERACIÓN NATURAL. - GÓMEZ-SÁNCHEZ, E; GONZÁLEZ-OCHOA, A I; TORRES, P; DE LAS HERAS, J; SIMARRO, E (III Congreso Forestal Español, 2001)
In order to obtain plant of good quality for afforestation of burned zones, seedlings inoculation has been carried out in nursery with different species of ectomycorrhizal fungi, using different inoculation techniques. The inoculated seedlings belong to three Mediterranean tree species with high colonizer capability of burned zones: Pinus halepensis, Pinus pinaster and Quercus ilex subsp. ballota. All of them were produced in container. The fungi used were: Lactarius deliciosus, L. sanguifluus, Suillus bellinii, S. collinitus, S. mediterraneensis and Pisolithus tinctorius for pine species; and Tuber melanosporum in the case of holm-oak. For Pinus inoculation it was made mycelial slurries and spore suspensions. For Quercus inoculation it was produced spore suspension. The experiment was carried out in two different nurseries, and it was evaluated the seedling heights and the mycorrhization percentage obtained using several parameters. Our results let optimize the application of mycorrhizal techniques in nurseries in order to produced mycorrhized plants with commercial aims.
Keywords: ectomycorrhizal fungi; Inoculation; mediterranean burned forests